Analysis of Activated Carbon Monolith Derived from Carrot Juice Waste for Supercapacitor Electrode Application - Dewi Ramayani; Yanuar Hamzah; Erman Taer; Novi Yanti; Afriwandi Apriwandi (Journal of Aceh Physics Society, 2021)
Abstrak. Pengembangan sistem penyimpanan energi elektrokimia yang efektif dan efisien menjadi sangat penting pada era evolusi teknologi dan industri modern saat ini. Penelitian ini mengemukakan karbon aktif sebagai bahan dasar material elektroda untuk diaplikasikan pada piranti penyimpan energi, khsusunya superkapasitor melalui analisa densitas, X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) dan Cyclic Voltammetry (CV). Karbon aktif berbentuk monolit disiapkan dari ampas jus wortel melalui pendekatan pirolisis satu tahap terintegrasi dan aktivasi kimia KOH. Proses pirolisis satu tahap terintegrasi dilakukan melalui penggabungan karbonisasi dan aktivasi fisika dalam atmosfer gas N2/CO2. Berdasarkan analisis data, karbon aktif menunjukkan sifat amorf yang normal dan sifat porositas terkonfirmasi. Lebih lanjut, sifat elekrokimia dievaluasi menggunakan metode Cyclic Voltammetry (CV) pada sistem dua elektroda. Kapasitansi spesifik yang dihasilkan sebesar 155 F/g dalam elektrolit 1 M H2SO4 dengan energi spesifik dan daya spesifik adalah 21,52 Wh/kg dan 77,57 W/kg. Berdasarkan analisa ini maka ampas jus wortel terkonfirmasi berpotensi sebagai karbon aktif untuk elektroda yang diaplikasikan dalam piranti penyimpan energi superkapasitor.Abstract. The development of an effective and efficient electrochemical energy storage system is very important in today's era of technological evolution and the modern industry. This research suggests that activated carbon is the raw material for electrode materials to be applied to energy storage devices, especially supercapacitors through density analysis, X-ray diffraction (XRD), Fourier Transform Infrared (FTIR), and Cyclic Voltammetry (CV). Activated carbon in the monolith form derived from carrot juice waste was prepared through a one-stage integrated pyrolysis approach and chemical activation of KOH. An integrated one-stage pyrolysis process was carried out by combining carbonization and physical activation in an N2/CO2 gas atmosphere. Based on data analysis, activated carbon performed normal amorphous behavior with confirmed porosity features. Furthermore, the electrochemical properties were evaluated using the Cyclic Voltammetry (CV) method at the two-electrode system. The specific capacitance was found as high as 155 F/g in the 1 M H2SO4 aqueous electrolyte with specific energy and specific power as high as 21.52 Wh/kg and 77.57 W/kg, respectively. Based on this analysis, the carrot juice waste has been confirmed to have the potential as activated carbon for the electrodes applied in supercapacitor energy storage technology.Keywords: Carrot Juice Waste, Activated Carbon, Electrode Materials, Supercapacitor